2014
DOI: 10.1080/02619768.2014.912628
|View full text |Cite
|
Sign up to set email alerts
|

Preparing teacher candidates for family–school partnerships

Abstract: Previous research indicates that, while parent involvement promotes student achievement, how teacher candidates are prepared to establish family-school partnerships (FSP) is not well documented and the roles of teacher educators are often neglected. Explorative studies including curriculum analysis and focus groups of primary and secondary teacher candidates and teacher educators were conducted in three universities, one each in the Netherlands, Belgium and the USA. Data collection was designed to identify opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 29 publications
0
34
0
12
Order By: Relevance
“…More recent research has concluded that there remains a lack of attention to FSP in ITE (Epstein 2013;Willemse et al 2016). As Epstein (2013, 117) emphasises: 'More professors of education should feel comfortable and competent conducting a comprehensive course using an updated text that includes research readings, topics to discuss in class, field experiences, and short and long-term projects ' . de Bruïne et al (2014) also describe the struggle of teacher educators to improve the curriculum in times of already overloaded programmes and Evans (2013, see also Willemse et al 2017) in particular notice a lack of attention to FSP in ITE programmes for secondary education.…”
mentioning
confidence: 99%
“…More recent research has concluded that there remains a lack of attention to FSP in ITE (Epstein 2013;Willemse et al 2016). As Epstein (2013, 117) emphasises: 'More professors of education should feel comfortable and competent conducting a comprehensive course using an updated text that includes research readings, topics to discuss in class, field experiences, and short and long-term projects ' . de Bruïne et al (2014) also describe the struggle of teacher educators to improve the curriculum in times of already overloaded programmes and Evans (2013, see also Willemse et al 2017) in particular notice a lack of attention to FSP in ITE programmes for secondary education.…”
mentioning
confidence: 99%
“…A narrative analysis shows the policy debate moving from the relation between social class and school success in the 1960s, through the discourse of accountability in the 1970s, marketization in the 1980s and 1990s, to a recent interest in direct interventions into parenting and the regulation of school relations with parents (Bridges, 2010). In the US, collaboration with parents is legally required for pre-service teachers' graduation (De Bruı¨ne et al, 2014;Willemse et al, 2016). Moreover, there is a strong mobilization of parents at the grassroots level to advance a school reform agenda (Manno, 2012).…”
Section: Policy Discussionmentioning
confidence: 99%
“…There is a positive change in teachers' attitude towards school-family partnerships after completing such programmes (De Bruı¨ne et al, 2014;Hedges and Lee, 2010). Treatment group members articulated a theoretical and practical understanding of the benefits of family involvement.…”
Section: Empirical Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, an increased level of PI in the education of their children has been reported in different societies. Hence, several studies examining the aspects of PI in children's education and the phenomenon of school-family partnership exist (Addi-Raccah & Ainhoren, 2009;De Bruïne et al, 2014;Dor & Rucker-Naidu, 2012;McAnnof-Gumbs, 2006;Pereira & Serrano, 2014;Shamay, 2008;Sauto-Manning & Swick, 2006).…”
Section: Introductionmentioning
confidence: 99%